The Effect of Audit Renewal Strategy and Best Audit Practice on Audit Performance: An Empirical Investigation of Certified Public Accountants (CPAs) in Thailand - Jiraphatthanaponsin, Thanniti; Boonlua, Sutana; Janjarasjit, Suparak (JOURNAL OF SOUTHERN TECHNOLOGY, 2018)
The purpose of this study is to examine the effect of audit renewal strategy and best audit practice on audit performance via the moderating influences which include transformational climate and audit experience usefulness. Audit renewal strategy is recognized as the auditor’s capability of transforms; method, concept, process, and learning to improve a competitive advantage permanently and promote audit performance. It is the key procedure of substantial transformation with respect to the main organizational characteristic of sustaining a firm’s a long-term prospects and survivability. Likewise, audit renewal strategy has a positive impact on audit performance based on dynamic capabilities theory. Data were collected from 391 CPAs in Thailand by questionnaire mail survey. The statistic used to analyze is the ordinary least square regression. The results of OLS regression indicates that audit renewal strategy positively affects best audit practice and audit performance. Besides, the findings also indicate that transformational climate positively moderates the relationships between audit renewal strategy and best audit practice. The best audit practice significantly influences audit performance. Especially, the result shows that audit tenure has a negative influence on audit performance. It can be interpreted that the audit tenure in the context of Thailand reduces audit performance because new auditor may be lack experience and knowledge of the client’s firm compared with the old auditor. Finally, theoretical and managerial contributions, conclusion, and suggestions for future research are discussed as well.